1988
DOI: 10.1007/bf00916949
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of soluble interleukin-2 receptor in patients with systemic lupus erythematosus and rheumatoid arthritis

Abstract: In this study we investigated the serum levels of a released soluble form of the interleukin-2 receptor (sIL-2R) in 42 patients with rheumatoid arthritis and in 12 cases of systemic lupus erythematosus. Data were evaluated in relationship to the clinical phase and compared with those observed in normal controls (N = 56) and in osteoarthritis (N = 7). Increased levels were observed in both rheumatoid arthritis (mean +/- SE, 604 +/- 49 U/ml) and systemic lupus erythematosus (1438 +/- 481 U/ml). These values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 37 publications
5
27
0
Order By: Relevance
“…Although the exact immunological role of sIL-2R is not well-established, it may serve as a marker of disease activity in patients with systemic lupus erythematosus, rheumatoid arthritis [7], haematological malignancies [8] and pulmonary disorders, such as asthma [9], lung cancer [10] and tuberculosis (TB) [11]. In patients with old inactive TB, the serum sIL-2R levels were not significantly different from those of normal control subjects.…”
mentioning
confidence: 99%
“…Although the exact immunological role of sIL-2R is not well-established, it may serve as a marker of disease activity in patients with systemic lupus erythematosus, rheumatoid arthritis [7], haematological malignancies [8] and pulmonary disorders, such as asthma [9], lung cancer [10] and tuberculosis (TB) [11]. In patients with old inactive TB, the serum sIL-2R levels were not significantly different from those of normal control subjects.…”
mentioning
confidence: 99%
“…Increased serum sIL-2R levels have been reported in several autoimmune disorders, such as rheumatoid arthritis (Semenzato e;a/,, 1988;Symons e/a/,, 1988, Manoussakise^a/,, 1989), Sjogren's syndrome (Manoussakis et al, 1989), active and inactive SLE (Semenzato et al, 1988;Manoussakis et al, 1989), as well as murine lupus (Balderas et al, 1987), Since activated T lymphocytes (Uchiyama, Broder & Waldmann, 1981), B cells (Waldmann et al, 1984) and monocytes/macrophages (Hermann et al, 1985) express IL-2R, the most important cell source of elevated circulating sIL-2R levels in PSS patients remains to be determined. However, the report that at least in vitro, the amount of released sIL-2R by stimulated B lymphocytes and monocytes is less than that produced by activated T lymphocytes (Nelson et al, 1986) seems to indicate that the in vivo measurement of sIL-2R provides an accurate index of T cell activation only.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that sIL-2R levels offer a rapid, reliable and noninvasive measure of disease activity, response to therapy and, in some cases, prognosis in a broad spectrum of conditions associated with T-or B-cell immune activation [11]. Similarly, sIL-2R levels have been evaluated in gynecologic conditions such as endometriosis, cervical cancer in association with HPV and in other genital cancers [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of sIL-2R can be measured easily because a part of it is proteolytically cleaved and is found in serum [10]. Previous studies have demonstrated elevated serum levels of sIL-2R in various autoimmune disorders such as rheumatoid arthritis, systemic lupus erythematosus or Kawasaki disease, among transplant recipients who subsequently reject their graft, and in individuals with viral infections, including HIV and hepatitis, or hematological and lung tumors, as well as precancer and cancer of the uterine cervix [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%